The Validity and Reliability of the MacNew Heart Disease Health Related Quality of Life Questionnaire: The Indonesian Version - Nur Basuki; Doa El-Ansary; Stefan Höfer; Bambang Dwiputra; Nantinee Nualnim (Acta Medica Indonesiana)
Background: The MacNew heart disease health related quality of life tool is used widely in the cardiac populations to evaluate the impact of disease and intervention including rehabilitation. In addition to the English version, it is also available for several other languages except the Indonesian language. Therefore, the purpose of this study were 1) to translate the MacNew questionnaire from the English version to the Indonesian language and 2) to estimate the preliminary validity and reliability of the Indonesian MacNew for patients with coronary artery disease. Methods: Forward and backward translation procedure was used to develop the Indonesian MacNew. The Indonesian MacNew was administered to 24 patients after one week of revascularization surgery. Reliability was assessed by internal consistency and test-retest reliability. To evaluate concurrent validity, the correlation of the compatible domain of the Indonesian MacNew and SF-36 was assessed. Results: Internal consistency reliability of the Indonesian MacNew was confirmed with Cronbach’s α of the global scale and all three subscales exceeding 0.95. Test- retest reliability was acceptable with intraclass correlation coefficient of 0.66 for the global score. Furthermore, an acceptable concurrent validity was established with statistically significant correlation between Indonesian MacNew and SF-36 (pearson correlation ranging from 0.47 to 0.71). Conclusion: The first results of the Indonesian MacNew indicate acceptable validity and reliability as a measurement tool to assess health related quality of life of Indonesian patients with coronary artery disease.